2016
DOI: 10.3892/ol.2016.5040
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the diagnostic utility of urinary midkine for the detection of bladder cancer

Abstract: As it has been demonstrated previously that midkine (also known as neurite growth-promoting factor 2) protein levels in urine of bladder cancer (BCa) patients are increased compared to healthy controls, the present study validated the diagnostic utility of midkine in an independent patient cohort and compared the observed values with voided urine cytology (VUC), which is the current reference standard for non-invasive diagnosis of BCa. Voided urine samples were prospectively collected from 92 BCa patients and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Serum and plasma levels of MDK are evidently correlated with diagnosis and prognosis in cancer patients (higher MDK level usually suggests tumor occurrence and worse prognosis). Furthermore, MDK was detected in urine, and its high expression in urine might be correlated with worse prognosis in patients with bladder cancer [ 15 , 33 ]. Moreover, MDK was associated with relapse free survival in patients with cancers [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum and plasma levels of MDK are evidently correlated with diagnosis and prognosis in cancer patients (higher MDK level usually suggests tumor occurrence and worse prognosis). Furthermore, MDK was detected in urine, and its high expression in urine might be correlated with worse prognosis in patients with bladder cancer [ 15 , 33 ]. Moreover, MDK was associated with relapse free survival in patients with cancers [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In tumors, MDK can promote tumor cells differentiation, proliferation, anti-apoptosis, chemoresistance, transformation and epithelial-mesenchymal transition (EMT) [ 4 7 ]. High MDK protein expression has been reported in several cancer types and associated with the cancer progression, including gastric cancer [ 8 ], pancreatic cancer [ 9 ], lung cancer [ 10 ], breast cancer [ 11 ], colorectal carcinoma [ 12 ], esophageal cancer [ 13 ], hepatocellular carcinoma [ 14 ] and bladder cancer [ 15 ]. An important example, MDK is overexpressed in about 50% of pancreatic cancer patients, and participates in the tumor cells chemotherapy resistance through the Notch 2 signaling pathway [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, the cellular source of MK in the vascular system has not been fully elucidated. Elevated MK serum levels are found in patients with different tumor entities and have been shown to correlate with poor prognosis and recurrence after tumor removal [ 2 , 3 , 4 ]. The tumor cells may be the source of MK in this case, as malignant tissue often shows high MK expression [ 5 ].…”
Section: Midkinementioning
confidence: 99%
“…However, multiple studies during the last three decades clearly indicated a functional impact of MK on the adult organism as well. By far, most of the studies on MK addressed its role in malignant diseases and suggested a detrimental effect for the host [ 2 , 3 , 4 , 5 ]. A significant part of the literature on MK has shown its ability to promote inflammatory responses.…”
Section: Introductionmentioning
confidence: 99%
“…Midkine (MDK), a heparin-binding growth factor, was first identified as a highly expressed factor involved in embryonic development ( 12 ). MDK has been reported to have important roles in the survival, growth and migration of cells, which may contribute to oncogenesis and tumor progression in numerous types of cancer ( 13 18 ). Several studies have demonstrated that MDK mediates drug resistance.…”
Section: Introductionmentioning
confidence: 99%